2014
DOI: 10.1371/journal.pone.0090974
|View full text |Cite
|
Sign up to set email alerts
|

Low Prevalence of Pneumococcal Carriage and High Serotype and Genotype Diversity among Adults over 60 Years of Age Living in Portugal

Abstract: Pneumococcal disease is frequent at the extremes of age. While several studies have looked at colonization among young children, much less is known among the elderly. We aimed to evaluate pneumococcal carriage among elderly adults living in Portugal. Between April 2010 and December 2012, nasopharyngeal and oropharyngeal swabs of adults over 60 years of age, living in an urban area (n = 1,945) or in a rural area (n = 1,416), were obtained. Pneumococci were isolated by culture-based standard procedures, identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
64
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(78 citation statements)
references
References 40 publications
(51 reference statements)
13
64
1
Order By: Relevance
“…Furthermore, S. pneumoniae carriage rates positively correlate with age in young children and then begin to drop in adults (3,6,7). These results have been confirmed in epidemiological studies conducted in several locations around the world (7)(8)(9).…”
supporting
confidence: 56%
“…Furthermore, S. pneumoniae carriage rates positively correlate with age in young children and then begin to drop in adults (3,6,7). These results have been confirmed in epidemiological studies conducted in several locations around the world (7)(8)(9).…”
supporting
confidence: 56%
“…In the present study, as reported for non-immunocompromised patients [33][34][35][36], the colonization rate was less than 5% of the SOT recipients. This rate is considerably lower than that observed in healthy children (up to 54%) [37,38].…”
Section: Discussionsupporting
confidence: 63%
“…Therefore, the absence of glucose in the nasopharynx of colonized adults may help to explain why colonization does not typically result in an overt inflammatory state. Additionally, increases in glucose concentration within the nasopharynx-for example, as a result of virusinduced inflammation or even uncontrolled diabetes-may further explain why individuals with these conditions are vulnerable to IPD (62,64,65). Thus, catabolite repression is possibly a key event in initiating a pathogenic program of S. pneumoniae.…”
Section: Discussionmentioning
confidence: 99%